Infections caused by carbapenem‐resistant Klebsiella pneumoniae among patients in intensive care units in Greece: a multi‐centre study on clinical outcome and therapeutic options. (30th August 2013) - Kontopidou, F.; Giamarellou, H.; Katerelos, P.; Maragos, A.; Kioumis, I.; Trikka‐Graphakos, E.; Valakis, C.; Maltezou, H. C.; Cantón, R.; ,
Abstract Infections due to carbapenem‐resistant Klebsiella pneumoniae (CR‐KP) have emerged as a public health problem worldwide given their spread dynamics and the limited therapeutic options. Our aim was to study the clinical outcome of patients with CR‐KP infections in relation to antimicrobial treatment. CR‐KP infections that occurred in a 10‐month period (September 2009 to June 2010) in patients admitted to 19 intensive care units all over Greece were studied. A total of 127 CR‐KP infections were reported. Central venous catheter bacteraemia was the most frequent infection, followed by ventilator‐associated pneumonia (39 (30.7%) and 35 (27.6%) cases, respectively). Resistance to colistin, tigecycline, gentamicin and amikacin was detected in 20%, 33%, 21% and 64% of isolates, respectively. Regarding treatment, 107 cases received active treatment, including 1 or ≥2 active antibiotics in 65 (60.7%) and 42 (39.3%) cases, respectively. The most frequent combination was colistin plus aminoglycoside and tigecycline plus aminoglycoside (17 and 11 cases, respectively). Forty‐eight (45.2%) of the cases that received active treatment were considered clinical failures, with 23.5% mortality at 14 days. Logistic regression analysis revealed that age ≤55 years, non‐immunocompromised patients and patients who received colistin had higher successful response rates, while patients ≤55 years old had lower mortality rates at 14 days after the introduction of active treatment. CR‐KP infections are associated with a significant clinical failure rate. Colistin remains a valuable antimicrobial agent for treating these infections, while the rise of resistance to the last available antibiotics further limits treatment options.